A SUPPLEMENT TOWARDS CREATION OF RURAL RAGIONALIZATION CONCEPT IN THE REPUBLIC OF SERBIA - Stojiljković, Dragi; Njegovan, Nikola (Economics of Agriculture, 2010)
The paper is discussing the problems of defining the rural аreas within the Republic of Serbia and the relative importance of rural versus urban areas. The authors try to examine determinants of overall socio-economic development (local authority administrative districts). They suggest most conveniant rural indicators that could be calculated and implemented at the regional level as well as the composte indicator as overal measure. Based on that analysis the rural and urban areas are identified mainly using the level of existing rurality and its relative importance. At the end, the particular and/or averall results as a base for the creation and implementation of different rural policy/ies in Republic of Serbia, has been discussed.